2017
DOI: 10.1002/jcla.22262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic values of Club cell protein 16 (CC16) in critical care patients with acute respiratory distress syndrome

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is a critical condition characterized by bilateral pulmonary infiltrates and severe hypoxemia. This study aimed to evaluate the diagnostic and prognostic values of Club cell protein 16 (CC16) in critical care patients with ARDS.MethodsIn this retrospective observational study, 83 patients with ARDS and 129 non‐ARDS patients on ICU admission were enrolled. The differences in serum CC16 and other laboratory indicators between two groups were analyzed. The sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
7
32
1
3
Order By: Relevance
“…According to previous research by our group, increased serum CC16 levels can help clinicians identify ARDS in critical care patients with normal renal function [ 10 ], and this finding was confirmed in the present study. However, RD, whether in the form of AKI or CKD, also was found to raise the serum CC16 level, reducing the specificity of serum CC16 for ARDS and altering the diagnostic cutoff points for ARDS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to previous research by our group, increased serum CC16 levels can help clinicians identify ARDS in critical care patients with normal renal function [ 10 ], and this finding was confirmed in the present study. However, RD, whether in the form of AKI or CKD, also was found to raise the serum CC16 level, reducing the specificity of serum CC16 for ARDS and altering the diagnostic cutoff points for ARDS.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, we found that an increased serum CC16 level (cutoff point at ≥33.3 ng/ml) can predict the onset of ARDS and is negatively correlated with the PaO 2 /FiO 2 ratio among ARDS patients [ 10 ]. However, we later observed that renal dysfunction (RD) separately raises the serum CC16 level.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous clinical research showed that CC16 can serve as a highly specific biomarker for the diagnosis and treatment of ARDS ( Lin et al., 2018 ). In addition, increasing the CC16 content in the serum or lung tissues can inhibit the expression of various inflammatory factors, such as HMGB1, thereby reducing the inflammatory response ( Pang et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 101 polytrauma patients with severe chest trauma, higher levels of CC-16 were found at admission and day 2 in patients who developed pneumonia compared with patients without pneumonia 17. Furthermore, patients with ARDS from multiple causes including trauma showed higher levels of CC-16 compared with patients without ARDS 39. In this study, 28.1% of patients with MODS also fulfilled the ARDS criteria, which could partly explain the association of CC-16 with the development of MODS in this study.…”
Section: Discussionmentioning
confidence: 99%